The adsorption capacity of root exudate organic carbon onto clay mineral surface changes depending on clay mineral types and organic carbon composition - Ndzana, Georges Martial; Zhang, Yueling; Yao, Shuihong; Hamer, Ute; Zhang, Bin (Rhizosphere, 2022)
Organic compounds released by plant roots may be protected from microbial decomposition through mineral-organic association. Yet, the adsorption characteristics of root exudates organic compounds by 2:1 clay minerals and the underlying mechanisms remain not fully understood. This study considers glucose and oxalic acid separately and added into quartz, illite, vermiculite, and montmorillonite in solution at different concentrations and shaking for 4 h before performing total organic carbon (TOC), Fourier Transformation Infrared (FTIR) spectroscopy, conventional X-Ray Diffraction (XRD) analysis and Brunauer-Emmett-Teller measurement with N2 gas adsorption. According to the results, the Langmuir-Freundlich isotherm curves showed that quartz and the 2:1 clay minerals can adsorb oxalic acid more than glucose and the adsorption capacity fell in the order of quartz < illite < vermiculite < montmorillonite for each compound. The glucose and oxalic acid adsorption increased with the decrease of main mineral reflection (d001), external specific surface area (ESSA), and the reduction of specific mineral functional groups, such as OH–Mg2–Al, Al–OH, Si–O, and Si–O–Si. In addition, the FWHM increased for montmorillonite and vermiculite following the addition of glucose and oxalic acid. These results indicated that the adsorption of either glucose or oxalic acid caused a modification of the crystalline structures of the clay minerals. The high signal of the H2O band for glucose addition and new bands of oxalic acid (COO−; CO−, COOH−) for oxalic acid addition were observed, indicating that glucose and oxalic acid were entrapped into micropores of the minerals, including quartz through hydrogen bonding and oxalic acid functional groups, respectively. Our study suggested that the adsorption of glucose and oxalic acid were controlled by the clay mineral properties (types, external surface areas, and modified crystalline structure), and organic carbon types. This study reveals the characteristics of the adsorption of root exudate organic compounds by clay minerals surface and highlights the role of 2:1 clay minerals in the stabilization of root exudate organic compounds. •Glucose and oxalic acid can be adsorbed onto quartz and 2:1 clay mineral.•Hydrogen bonding was the main mechanism for glucose adsorption.•Mineral-oxalic acid functional groups complex was the main adsorption mechanism for oxalic acid.•Adsorption of glucose and oxalic acid cause defects in clay mineral crystalline structure.•Mineral properties and organic carbon types control the adsorption capacity of clay minerals.